Evaluation of particulate matter emissions from non-passenger diesel vehicles in Qatar - Hanadi Al-Thani (8350050) (2020)
Road traffic is one of the main sources of particulate matter (PM) in the atmosphere. Despite itsimportance, there are significant challenges in the quantitative evaluation of its contribution toairborne concentrations. In order to propose effective mitigation scenarios, the proportions of PMtraffic emissions, whether they are exhaust or non-exhaust emissions, should be evaluated for anygiven geographical location. In this work, we report on the first study to evaluate particulatematter emissions from all registered heavy duty diesel vehicles in Qatar. The study was applied toan active traffic zone in urban Doha. Dust samples were collected and characterized for theirshape and size distribution. It was found that the particle size ranged from few to 600μm with thedominance of small size fraction (less than 100μm). In-situ elemental composition analysis wasconducted for side and main roads traffic dust, and compared with non-traffic PM. The resultswere used for the evaluation of the enrichment factor and preliminary source apportionment. Theenrichment factor of anthropogenic elements amounted to 350. The traffic source based on sulfurelemental fingerprint was almost 5 times higher in main roads compared with the samples fromnon-traffic locations. Moreover, PM exhaust and non-exhaust emissions (tyre wear, brake wear androad dust resuspension) were evaluated. It was found that the majority of the dust was generatedfrom tyre wear with 33% followed by road dust resuspension (31%), brake wear (19%) and thenexhaust emissions with 17%. The low contribution of exhaust PM10emissions was due to the factthat the majority of the registered vehicle models were recently made and equipped with efficientexhaust PM reduction technologies.Implication: This study reports on the first results related to the evaluation of PM emission fromall registered diesel heavy duty vehicles in Qatar. In-situ XRF elemental analysis from main, sideroads as well as non-traffic dust samples was conducted. Several characterization techniques wereimplemented and the results show that the majority of the dust was generated from tyre wear,followed by road dust resuspension and then brake wear; whereas exhaust emissions weretremendously reduced since the majority of the registered vehicle models were recently madeand equipped with efficient exhaust PM reduction technologies. This implies that policy makersshould place stringent measures on old vehicle license renewals and encourage the use of metroand public transportation. Other Information Published in: Journal of the Air & Waste Management Association License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1080/10962247.2019.1704939